2007
DOI: 10.1111/j.1530-0277.2007.00344.x
|View full text |Cite
|
Sign up to set email alerts
|

Antiglutamatergic Strategies for Ethanol Detoxification: Comparison With Placebo and Diazepam

Abstract: Background: Benzodiazepines are the standard pharmacotherapies for ethanol detoxification, but concerns about their abuse potential and negative effects upon the transition to alcohol abstinence drive the search for new treatments. Glutamatergic activation and glutamate receptor up-regulation contribute to ethanol dependence and withdrawal. This study compared 3 antiglutamatergic strategies for ethanol detoxification with placebo and to the benzodiazepine, diazepam: the glutamate release inhibitor, lamotrigine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
75
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 117 publications
(79 citation statements)
references
References 49 publications
3
75
0
1
Order By: Relevance
“…The present findings are in concurrence with Krupitsky et al (2007), who demonstrated the superior efficacy of three antiglutamatergic strategies, the glutamate release inhibitor, lamotrigine; the N-methyl-D-aspartate glutamate receptor antagonist, memantine; and the AMPA/kainite receptor inhibitor, topiramate, in ameliorating observer-rated and self-rated withdrawal severity, dysphoric mood, and supplementary diazepam administration in a placebo-controlled study (Krupitsky et al, 2007). A major advantage of ceftriaxone compared with these other antiglutamatergic medications and benzodiazapines is the relatively benign side effect profile.…”
Section: Discussionsupporting
confidence: 92%
“…The present findings are in concurrence with Krupitsky et al (2007), who demonstrated the superior efficacy of three antiglutamatergic strategies, the glutamate release inhibitor, lamotrigine; the N-methyl-D-aspartate glutamate receptor antagonist, memantine; and the AMPA/kainite receptor inhibitor, topiramate, in ameliorating observer-rated and self-rated withdrawal severity, dysphoric mood, and supplementary diazepam administration in a placebo-controlled study (Krupitsky et al, 2007). A major advantage of ceftriaxone compared with these other antiglutamatergic medications and benzodiazapines is the relatively benign side effect profile.…”
Section: Discussionsupporting
confidence: 92%
“…Undergoing more than two detoxifications has been associated with poorer performance on some cognitive tasks although a causal link has not been proven (Duka et al, 2004;Loeber et al, 2010). Krupitsky et al (2007) (Ib) reported that a range of antiglutamatergic approaches such as memantine (NMDA antagonist), topiramate (AMPA/kainate inhibitor) or lamotrigine (glutamate release inhibitor) were efficacious in treating alcohol withdrawal similarly to diazepam. A Cochrane review ) (Ia) was cautious about anticonvulsants, stating that there was 'insufficient evidence in favour of anticonvulsants for treatment of alcohol withdrawal' although they seemed to have 'limited side effects' and 'might be effective for some symptoms', for example seizures.…”
Section: Management Of Withdrawal and Detoxificationmentioning
confidence: 99%
“…These agents include phenobarbital (up to 1500 mg to 2000 mg administered orally or intravenously on day 1 in patients with delirium 13 ); clomethiazole (not available intravenously, but for uncomplicated withdrawal, up to 2304 mg (12 capsules) can be administered orally in divided doses on day 1 7,25 ); midazolam (one study indicated a dose of up to 2800 mg over 50 days); carbamazepine (approximately 800 mg per day); and oxcarbazepine (approximately 900 mg per day). 7,[26][27][28] In patients who do not have a response to high doses of benzodiazepines (especially patients who are intubated), propofol may be administered (e.g., 0.3 to 1.25 mg per kilogram of body weight, up to 4 mg per kilogram per hour, for up to 48 hours). 20,26 Another adjunctive medication is dexmedetomidine, an α 2 -adrenergic agonist that is used in ICUs to produce a state in which the patient is sedated but arousable, with decreased sympathetic tone.…”
Section: Components Of Scale Most Severe Manifestationsmentioning
confidence: 99%